Effects of early weaning onto herb-clover mix on lamb carcass and meat quality characteristics : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Animal Science at Massey University, Palmerston North, New Zealand - Wong, Huai Xuan (Massey University, 2019)
After eight weeks of age, the lambs’ diet consists of only a small proportion of milk. Early weaning at 8-weeks of age onto high nutritive value forage crops, therefore, may be able to compensate for the removal of milk from the diet whilst maintaining lamb liveweight gains. It is crucial, however, to ensure there are no negative effects of early weaning on the yield of saleable meat and its quality. This study aimed to understand the effects of early weaning onto a herb-mix on carcass and meat quality characteristics. Ewes and their twin lambs (weighing at least 16kg) were allocated to one of three treatments: 1. Lambs with dams on grass (GRASS) (lambs; n=50; 𝑥̅ LW=17.0kg), 2. Lambs with dams on herb-mixes (HERB) (lambs; n=50; 𝑥̅ LW=17.2kg), 3. Lambs weaned onto herb-mixes (56-days old) and dams on grass (EARLY) (lambs; n=50; 𝑥̅ LW=16.4kg). At 12 weeks of age, all lambs were weaned and lambs with a liveweight of greater than 35kg were sent for slaughter (n=28; 𝑥̅ LW=36.9kg). The remaining lambs grazed together on ryegrass-based pasture for six weeks. After this period, lambs with a liveweight >35kg were sent for slaughter (n=93; 𝑥̅ LW=40.4). Hot-carcass weight and VIAscan estimates of GR soft tissue depth (tissue depth 110 mm from the midline on the 12th rib) and lean meat yields were obtained. Meat quality assessments were conducted to obtain pH, colour, water-holding capacity, intramuscular fat, sarcomere length and tenderness values. The average daily gain of lambs in the HERB treatment (307.0 ± 7.4g) were greater than those in the EARLY (255.8 ± 8.0g) and GRASS (267.8 ± 8.5g) treatments (P<0.05). The dressing out and lean meat yield did not differ among lambs of different treatments (P>0.05). The lambs in HERB treatment had greatest hot-carcass weight (17.4 ± 0.23kg) and GR soft tissue depth (8.2 ± 0.41mm) (P<0.05). The higher average daily gains, carcass weight and GR soft tissue depth of lambs on herb-mix is expected as it has a higher feeding value. Lambs in EARLY treatment had the greatest bone weight (P<0.05). Dissected fat weight, muscle-to-bone ratio and muscularity index was greatest in lambs from the HERB treatment (P<0.05). There was no difference across the treatments for intramuscular fat percentage, meat colour, drip loss, sarcomere length and shear force values (P>0.05). All treatments were associated with low shear force values (<5kg F). The results suggest that, when taken to a set weight, early weaning of lambs onto herb-clover mix did not appear to have any negative effects on carcass and meat quality characteristics. However, a smaller proportion of early weaned lambs may achieve a set slaughter weight at a set date compared to similar lambs with their dams on a high nutritive value forage. Early weaned lambs are likely to require more time for finishing to a set weight.
Figures 1-4 (=Kemp et al., 2010 Fig 1) & 1-5 (=Devine et al., 1993 Fig 1a) have been removed for copyright reasons.
Keywords: Lambs; Feeding and feeds; Growth; New Zealand; Lamb (Meat); Quality